Diagnóstico de infección por streptococcus agalactiae en gestantes - Aguilera Mosquera, Krystell Maitte (Machala : Universidad Técnica de Machala, 2021)
Introduction: There are many bacteria capable of proliferating and creating an imbalance in the normal microbiota of the vagina, in this case Streptococcus agalactiae is present in the gastrointestinal flora, the perineal area, the urethra and the rectovaginal tract, it can cause problems during the labor and are responsible for high perinatal morbidity and mortality and maternal morbidity. Objective: To identify the ideal diagnostic method for Streptococcus Agalactiae UTI in pregnant women. Methodology: This study is a bibliographic review, on the subject of this research, based on the search of scientific articles extracted from the database of: Pubmed, Scielo, ACOG, CDC and ELSEVIER, in the last 5 years . Conclusion: It is proposed to carry out a vaginal and rectal sample between weeks 35 and 37 of gestation, by means of a conventional culture, which allows us to isolate the bacteria and be able to carry out antibiotic susceptibility studies. Subsequently, different forms of study could be performed, from gram staining, catalase test, MALDI-TOF MS, hemolysis, phenotypic, chromogenic, CAMP, PYR, rtPCR tests, latex agglutination tests, nucleic acid amplification tests or implement the new molecular technological advances such as the BD geneohm strepB. The tests with the highest sensitivity and specificity were rtPCR, MALDI-TOF MS, NAAT and the new molecular techniques, but they have little study time, and in many laboratories they have little experience in their use.
Introducción: Existen muchas bacterias capaces de proliferar y crear un desequilibrio en el microbiota normal de la vagina, en este caso el Streptococcus agalactiae se encuentra presente en la flora gastrointestinal, el área perineal, la uretra y el tracto rectovaginal, puede causar problema durante el trabajo de parto y son causantes de una alta morbimortalidad perinatal y morbilidad materna. Objetivo: Identificar el método diagnóstico idóneo para ITU por Streptococcus Agalactiae en gestantes. Metodología: El presente estudio se trata de una revisión bibliográfica, sobre la temática de la presente investigación, basada en la pesquisa de artículos científicos extraídos de la base de datos de: Pubmed, Scielo, ACOG, CDC y ELSEVIER, en los últimos 5 años. Conclusión: Se propone la realización de una muestra vaginal y rectal entre las semanas 35 y 37 de gestación, por medio de un cultivo convencional, que nos permite aislar la bacteria y poder realizar estudios de susceptibilidad antibiótica. Posterior se podría realizar diferentes formas de estudio, desde tinción de gram, prueba de catalasa, MALDI-TOF MS, hemolisis, pruebas fenotípicas, cromogénicas, CAMP, PYR, rtPCR, pruebas de aglutinación en látex, pruebas de amplificación de ácidos nucleicos o implementar los nuevos avances tecnológicos moleculares como es el BD geneohm strepB. Las pruebas con mayor sensibilidad y especificidad fueron rtPCR, MALDI-TOF MS, NAAT y las nuevas técnicas moleculares, pero cuentan con poco tiempo de estudio, y en muchos laboratorios cuentan con poca experiencia en su utilización.
Keywords: STREPTOCOCCUS AGALACTIAE; VAGINAL AND RECTAL CULTURE; PREGNANT; DIAGNOSIS